The Effect of Changing Focal Trough in a Panoramic Device on the Accuracy of Distance Measurements - Mehrdad Abdinian; Atiehsadat Hashemian; Amir A Sameti (Wolters Kluwer Medknow Publications, 2018)
>Introduction: Magnification and distortion are the most important limitations of panoramic radiography. The aim of this study was to determine the effects of changing focal trough option of Planmeca SCARA 3 on the accuracy of linear distance measurements.Materials and Methods: In this in-vitro study, 28 pieces of gutta-percha were attached to the assumptive place of each lost root of an adult dry skull with average size and normal shape. The actual measurements were obtained by a digital caliper. The panoramic images of the skull were taken in six different sizes and shapes of focal trough. This procedure was repeated ten times with new gutta-percha. Paired t-test was used to compare the values of different actual and radiographic images of gutta-percha dimensions.Results: The mean difference [standard deviation (SD)] between actual measurement and panoramic radiography in the different groups was from 0.37 (1.1) to 0.58 (2.87) mm. The mean (SD) difference of linear measurements between real and radiographic images was 0.52 (0.43) mm in average size, V-shaped group, which was statistically and clinically significant (P = 0.00).Conclusion: Changing the focal trough option of Planmeca SCARA 3 has minimal effects on the accuracy of linear measurements in panoramic radiographs.